Effects of inspiratory muscle training on respiratory function, diaphragmatic thickness, balance control, exercise capacity and quality of life in people after stroke: A randomized controlled trial protocol - Fang Liu; Alice Y. M. Jones; Raymond C. C. Tsang; Timothy T. T. Yam; William W. N. Tsang (PLoS ONE, 2025)
Background Stroke is associated with diaphragmatic weakness and impaired respiratory function as well as balance impairment. The role of inspiratory muscle training (IMT) on improvement of respiratory muscle strength in people after stroke has been reported. However, the training intensity associated with optimal diaphragm recruitment and the relationship between the effect of IMT and other functions in this population remains uncertain. Purpose This randomized controlled trial (RCT) aims to explore the effects of a 4-week IMT program with training intensity at 50% maximum inspiratory pressure (MIP) (previously shown to be associated with maximal diaphragm contraction), on respiratory function, balance control, exercise capacity and quality of life (QOL) in people after stroke. Methods This is a patient- and assessor-blinded RCT. Eligible participants will be randomly allocated to the targeted-IMT group (with 50% MIP as the training intensity) or sham-IMT group (with 10% MIP as the training intensity). Both groups will also receive the same standardised hospital-based physical-rehabilitation protocol. All interventions will be implemented 5 days/week for 4 weeks. The primary outcome is the change of diaphragmatic thickness. Secondary outcomes are spirometry respiratory function, balance control, exercise capacity and QOL. Assessment will be conducted at baseline, post-intervention, and at 12th week follow-up. Data will be primarily analysed using repeated-measures ANOVA α=0.05. Discussion Results of this study will primarily inform the effect of IMT on lung function, balance control, exercise capacity and QOL in addition to physical rehabilitation, further the interplay between the change in diaphragm thickness, balance and QOL will be analysed in detail.